2017
DOI: 10.1007/s13205-017-0759-9
|View full text |Cite
|
Sign up to set email alerts
|

An efficient process for the transformation of betulin to betulinic acid by a strain of Bacillus megaterium

Abstract: Betulinic acid as a derivative of betulin is widely reported for its anti-HIV and antitumor activities. Betulin has three most significant positions, i.e., primary hydroxyl group at position C-28, secondary hydroxyl group at position C-3, and alkene moiety at position C-20, where chemical modifications were performed to yield pharmacologically more active derivatives. Bioconversion optimization was performed for the enhancement in the percentage of conversion using statistical approach by opting temperature, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The strain of B. megaterium has been found as an important bio-tool bacterium with wide application in food and medicine industry and agriculture [25][26][27][28][29][30]. It has exhibited biotransformation function by modifying natural products to obtain more active derives, such as converting betulin to betulinic acid with anti-HIV and antitumor activities, and bio-transforming ursolic acid to its derives with nitric oxide production inhibitory activity [26,29]. Herein seven compounds from them were identified by LC/(+)ESI-MS/MS analysis, among which transformation forms, inclusive of reduction of heptadione chain (adding 2 or 4 hydrogen atoms) and hydroxylation/demethylation/ demethoxylation of aromatic rings, were speculated.…”
Section: Discussionmentioning
confidence: 99%
“…The strain of B. megaterium has been found as an important bio-tool bacterium with wide application in food and medicine industry and agriculture [25][26][27][28][29][30]. It has exhibited biotransformation function by modifying natural products to obtain more active derives, such as converting betulin to betulinic acid with anti-HIV and antitumor activities, and bio-transforming ursolic acid to its derives with nitric oxide production inhibitory activity [26,29]. Herein seven compounds from them were identified by LC/(+)ESI-MS/MS analysis, among which transformation forms, inclusive of reduction of heptadione chain (adding 2 or 4 hydrogen atoms) and hydroxylation/demethylation/ demethoxylation of aromatic rings, were speculated.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid developments in metabolic engineering and synthetic biology provide alternative approaches for the increased production of natural products in microbial hosts [12][13][14][15]. The identification of newly identified microbes that convert betulin to BA is recently more intentioned [16], and metabolic engineering of key biosynthetic genes derived from plant sources has been reported as well. As a consequence, microbes that convert betulin to BA is recently more intentioned [16], and metabolic engineering of key biosynthetic genes derived from plant sources has been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of newly identified microbes that convert betulin to BA is recently more intentioned [16], and metabolic engineering of key biosynthetic genes derived from plant sources has been reported as well. As a consequence, microbes that convert betulin to BA is recently more intentioned [16], and metabolic engineering of key biosynthetic genes derived from plant sources has been reported as well. As a consequence, this review discusses recent developments in biotransformation and metabolic engineering for BA production.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, BA was mainly transformed from betulin by cultured resting cells [ 12 , 13 ]. In the present work, oleic acid and fungal elicitor from A. niger were proved to be effective inducers for BA accumulation in the submerged fermentation of I. obliquus .…”
Section: Discussionmentioning
confidence: 99%
“…Betulin is the precursor material of BA. In recent times, several reports have demonstrated that BA could be prepared through biotransformation process [ 11 , 12 , 13 ]. Meanwhile, betulin was used stimulatory agent to enhance mycelial biomass and production of exo-polysaccharides from I. obliquus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%